Knowledge and awareness about Iron deficiency and megaloblastic anaemia among blood donors: a study at rural based tertiary care hospital - Shah, Amar R.; Shethwala, Nimisha D.; Parmar, B. H. (International Journal of Research in Medical Sciences, 2017)
Background: Voluntary blood donation is promoted in order to make the blood banking safe and successful. Research in the area of blood donation has found that, iron stores are influenced by regular blood donation if dietary intake of iron is inadequate. Awareness and knowledge among blood donors regarding iron and B12 deficiency and its prevention is very much required. Objective: To assess the knowledge and awareness about iron deficiency and megaloblastic anaemia among blood donors. Methods: A cross sectional study was conducted among the 500 voluntary blood donors during the span of 1 year at one of the blood bank of tertiary care hospital using prestructured questionnaire on the various aspect of iron and B12 deficiency/folate deficiency anemia. The data was analysed with the help of Microsoft excel and SPSS. Results: Out of 500 blood donors, 15.6% donors were regular blood donor. It was observed 60% blood donors were having knowledge of anemia in general. Iron deficiency and vitamin B12 deficiency were known to 42% and 31.6% donors, respectively. Only 20% donors could able to answer the acceptable level of hemoglobin require for donating the blood. About 42% donors were aware about importance of iron, folate and vitamin B12 in maintaining normal hemoglobin level. Majority (82.7%) of regular blood donors were willing to get information regarding iron, folate and vitamin B12 deficiency. Conclusion: Significant lack of awareness regarding iron and vitamin B12 deficiency was observed in regular voluntary blood donors. The present study recommends the provision of health education on iron and vitamin B12 deficiency as well as Iron, folate and vitamin B12 rich foods to regular blood donor to prevent anaemia among them.